Essentials of pathophysiology for pharmacy - Zdanowicz, Martin M. (Boca Raton, Florida : CRC Press, 2003)
Presenting all the information your students need in an accessible layout, Essentials of Pathophysiology for Pharmacy will give students a practical understanding of the pathophysiologic basis of selected diseases while providing a rationale for subsequent drug therapy.
Ch. 1. Cellular injury Ch. 2. Cancer Ch. 3. Disorders of hemostasis and coagulation Ch. 4. Alterations in hematologic function and oxygen transport Ch. 5. Immune response and inflammation Ch. 6. Acquired immune deficiency syndrome (AIDS) Ch. 7. Diseases of the vascular system Ch. 8. Alterations in blood pressure Ch. 9. Diseases of the heart Ch. 10. Myocardial ischemia Ch. 11. Myocardial infarction Ch. 12. Heart failure and shock Ch. 13. Abnormalities of cardiac conduction Ch. 14. Disorders of the respiratory system Ch. 15. Abnormalities of the kidney and urinary tract Ch. 16. Gastrointestinal disorders Ch. 17. Disease of the liver and exocrine pancreas Ch. 18. Endocrine disorders Ch. 19. Diabetes mellitus
Includes bibliographical references and index.
Keywords: PHYSIOLOGY, PATHOLOGICAL